Determinação de boro em fertilizantes pela colorimetria de azometina-h modificada - Da Silva, Assunta Maria Marques [UNESP]; Graner, Celso Augusto Fessel [UNESP] (My University, 1996)
The present work studied the azomethine-H colorimetric method for boron determination to fertilizers analysis applications. The reagent azomethine-H needs lights conditions of reaction that, jointed to the big sensibility and specificity, diffused its use in boron's dosage in many materials. The most suitable experimental parameters were established for such colorimetry, and analysis conditions: standard curve between 0.200 e 2.25 mg. L-1 boron, in maximum absorption at 415nm, 1 cm cell and reading between 30 and 90 minutes standing after the final homogenization of the boron's solution in analyse and with dye reactive (azomethine H 0,90 % m/v solution at buffer ammonium acetate 1,82 mol. L-1 - potassium acetate 0,10 mol. L-1 - acetic acid 1,67 mol. L-1-EDTA 2,7. 10-2 mol. L-1-NTA 2,1 .10-2 mol. L-1pH 5,5). Statistics analysis of the results didn't present big differences when the same results were got by the colorimetric method offered and by the potentiometric, from AOAC, whatever in manufactured fertilizers or in lab sintetized fertilizers.
The azomethine-H colorimetric method modified of boron determination at fertilizers
Keywords: Azomethine-H; Boron; Colorimetry; Fertilizer